Perbandingan Pengendalian Keuangan Pada Usaha Mikro Kecil Menengah (UMKM) Ice Jelly Potter Dan Keripik Singkong Di Kabupaten Bungo - Muhammad Farikin; Addiarrahman Addiarrahman; Lidya Anggraeni (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
This study aims to determine and compare how the financial control of ice jelly potter and cassava chips in financial control and to find out the shortcomings if they do not use financial control. This study uses a qualitative approach. The data sources used are primary and secondary data sources. While the data collection techniques used in this study were observation, interviews, and documentation. The results of the study indicate that in terms of financial control, the ice jelly potter business has implemented financial control although it has not been maximized which includes financial management (budgeting, recording, reporting, and financial control). This is a plus for UMKM because they have implemented financial controls as well as future steps that will be taken to become more knowledgeable, and can assist in decision making in the future. The factors that become a shortage of cassava chips business in running a business if they do not use financial control (financial management) are not knowing the next steps to be taken, not being able to develop a business, not knowing whether the business is profitable or detrimental. Therefore, financial control is very important in running a business.